Pengaruh Perceived Organizational Support, Kepuasan Kerja dan Organizational Citizenship Behavior terhadap Kinerja Pegawai Inspektorat Daerah Kabupaten Malang - Suhari, Didik; Mustapita, Arini Fitria; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of Perceived Organizational Support, Job Satisfaction and Organizational Citizenship Behavior on the performance of Malang Regency Regional Inspectorate employees. This research method uses quantitative methods. The population used was ASN employees of the Malang Regency Regional Inspectorate and 52 respondents were obtained using a saturated sampling technique. The data collection method uses an online questionnaire. The data analysis technique used is multiple linear regression analysis with the IBM SPSS Statistics 27 program. The research results show that Perceived Organizational Support, Job Satisfaction and Organizational Citizenship Behavior simultaneously have a positive and significant effect on employee performance. Partially Perceived Organizational Support has a positive and significant effect on employee performance, partial job satisfaction has a positive and significant effect on employee performance, and partial Organizational Citizenship Behavior has no significant effect on employee performance. Keywords: Employee Performance, Perceived Organizational Support, Job Satisfaction And Organizational Citizenship Behavior